A concrete coating resistant to chloride ion attack and a method for its production
Patent Information
- Application Number
- CN202611419738.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-23
AI Technical Summary
然而,碳点因粒径极小、表面能高,在水泥基强碱、高离子强度体系中极易发生严重团聚,难以保持纳米尺度的分散状态,其吸附优势在实际工程中难以有效发挥
[0025]1、首创硅灰预分散、共价键接枝分散策略,突破了单一分散手段的局限,确保了LDHs层间交换通道的充分开放和CDs纳米尺度的均匀分布,为二者功能协同发挥奠定了结构基础,从根本上解决LDHs与CDs在水泥基体系中的团聚难题;
Smart Images

Figure CN122958201A_ABST
Abstract
Description
Technical Field
[0001] This invention pertains to coatings and their preparation methods, specifically a concrete chloride ion resistant coating and its preparation method. Background Technology
[0002] Layered bimetallic hydroxides (LDHs) are ideal functional materials for improving the chloride ion erosion resistance of concrete due to their unique interlayer anion exchange capacity, which can embed corrosive chloride ions into the interlayer to achieve stable curing. However, LDHs face two major bottlenecks in practical applications: (1) There are strong electrostatic attraction and hydrogen bonding between the layers of LDH nanosheets, which are prone to stacking and agglomeration in aqueous or cement-based systems, resulting in blocked interlayer exchange channels and a significant decrease in ion exchange capacity; (2) The curing of chloride ions by LDHs mainly depends on the interlayer exchange mechanism, and the surface active sites are limited. The adsorption capacity and rate of a single curing pathway are difficult to meet the requirements of harsh service environments.
[0003] Carbon dots (CDs), as zero-dimensional carbon nanomaterials, are rich in oxygen-containing functional groups such as carboxyl (-COOH) and hydroxyl (-OH) groups on their surface, providing additional chloride ion adsorption sites. Theoretically, this could significantly improve the chloride ion curing performance of cement-based materials. However, due to their extremely small particle size and high surface energy, carbon dots are prone to severe agglomeration in cement-based strong alkaline and high ionic strength systems, making it difficult to maintain a nanoscale dispersion. Consequently, their adsorption advantages are difficult to effectively utilize in practical engineering. When CDs and LDHs coexist, the agglomeration problem is compounded, resulting in uneven dispersion. The chloride salt corrosion resistance and service durability of existing concrete need further improvement. Summary of the Invention
[0004] Purpose of the invention: In order to overcome the shortcomings of the prior art, the purpose of this invention is to provide a simple and controllable method for preparing a concrete anti-chloride ion erosion coating that avoids agglomeration. Another purpose of this invention is to provide a concrete anti-chloride ion erosion coating with good durability and fast capture rate.
[0005] Technical solution: The present invention provides a method for preparing a concrete coating resistant to chloride ion erosion, comprising the following steps:
[0006] Step 1: Disperse layered bimetallic hydroxide (LDHs) powder in deionized water to obtain an LDHs dispersion. Add a silane coupling agent to the LDHs dispersion, stir and heat to react, centrifuge, wash, and vacuum dry to obtain aminated LDHs. Prepare carbon dots rich in carboxyl groups on the surface using a hydrothermal or microwave method, prepare a CDs solution, and activate the carboxyl groups on the surface of the carbon dots using EDC and NHS coupling agents to obtain an activated CDs solution.
[0007] Step 2: Add the amination LDHs obtained in Step 1 to the silica fume dispersion and continue stirring and mixing to ensure that the silica fume particles are uniformly loaded on the surface of the LDHs, thereby obtaining silica fume pre-dispersed amination LDHs.
[0008] Step 3: Under stirring conditions, the activated CDs solution is added dropwise to the silica fume pre-dispersed aminated LDHs, and the CDs are grafted onto the surface of the LDHs layer through an amidation reaction. After the reaction is completed, the mixture is centrifuged, washed repeatedly with deionized water, and then freeze-dried to obtain the CDs@LDHs composite material.
[0009] Step 4: Mix the CDs@LDHs composite material obtained in Step 3 with cement and stir evenly to obtain a concrete composite coating slurry.
[0010] Step 5: Apply the composite coating slurry obtained in Step 4 to the surface of the steel reinforcement or concrete structure, and after curing, obtain a concrete anti-chloride ion erosion coating.
[0011] Furthermore, in step one, the concentration of the LDHs dispersion is 5~20 mg / mL.
[0012] Further, in step one, the mass ratio of the silane coupling agent to the layered bimetallic hydroxide in the LDHs dispersion is 1~3:10. Preferably, the silane coupling agent is KH-550.
[0013] Furthermore, in step one, the temperature of the stirring and heating reaction is 60~90℃, the time is 4~12 h, the stirring rate is 300~600 rpm, the temperature of vacuum drying is 40~60℃, and the drying time is 12~48 h.
[0014] Furthermore, in step one, the concentration of the CDs solution is 1~10 mg / mL, the molar ratio of NHS to EDC in the EDC / NHS coupling reagent is 1~2:1, and the pH of the activation treatment is 5.0~6.5.
[0015] Furthermore, in step one, the particle size of the carbon dots is 2~5 nm.
[0016] Furthermore, in step two, the silica fume dispersion is prepared by ultrasonic dispersion treatment of silica fume and deionized water at a mass ratio of 1:5~15.
[0017] Furthermore, in step two, the mass ratio of silica fume to aminated LDHs is 1:1~3.
[0018] Furthermore, in step three, the mass ratio of the activated CDs solution to the silica fume pre-dispersed aminated LDHs is 1:5~20, the amidation reaction temperature is 25~60℃, and the time is 4~24 h; the freeze-drying temperature is -50~-40℃, the vacuum degree is 10~50 Pa, and the time is 24~48 h.
[0019] Furthermore, in step four, the mass ratio of CDs@LDHs composite material to cement is 1:1~8, the cement is ordinary Portland cement, and the water-cement ratio is 0.3~0.5.
[0020] Furthermore, in step five, the curing temperature is 20~30℃, the relative humidity is ≥95%, the curing time is 7~28 days, and the coating is applied by spraying, brushing or scraping, with a coating thickness of 0.5~3 mm.
[0021] The concrete chloride ion erosion resistant coating obtained by the preparation method of the present invention has a chloride ion curing amount of more than 60.8 mg / g and a chloride ion curing rate of more than 64.5%.
[0022] Preparation principle: In steps one and two, the highly active silanol groups (Si-OH) on the surface of silica fume form a hydrogen bond network with the oxygen-containing functional groups and amino groups on the surface of LDHs, which stably anchors the composite material to the surface of silica fume particles, achieving a dual dispersion effect of physical isolation and chemical adsorption. Simultaneously, during the hydration process, silica fume can react with Ca(OH)2 to generate CSH gel, further densifying the coating's microstructure and enhancing the interfacial adhesion strength between the coating and the concrete substrate, thereby improving the physical barrier performance of the coating.
[0023] In step three, CDs are firmly anchored to the surface of LDHs layers via amide covalent bonds. The high strength of these covalent bonds prevents desorption and detachment under long-term hydration and service conditions. After grafting, CDs act as "nanospacers," physically preventing the direct stacking of LDH layers and ensuring fully open interlayer exchange channels, thereby accelerating chloride ion diffusion into the interlayer. Simultaneously, the abundant carboxyl (-COOH) and hydroxyl (-OH) functional groups on the CDs surface can additionally capture free chloride ions through electrostatic attraction and complexation, forming a dual-channel curing mode of "interlayer exchange + surface adsorption," significantly enhancing chloride ion curing ability.
[0024] Beneficial effects: Compared with the prior art, the present invention has the following significant features:
[0025] 1. The pioneering silica fume pre-dispersion and covalent bond grafting dispersion strategy breaks through the limitations of single dispersion methods, ensuring the full opening of interlayer exchange channels of LDHs and the uniform distribution of CDs at the nanoscale, laying the structural foundation for the synergistic function of the two and fundamentally solving the problem of aggregation of LDHs and CDs in cement-based systems.
[0026] 2. By covalently grafting CDs onto the surface of LDHs, the functional groups such as carboxyl and hydroxyl groups on the CDs surface provide a large number of additional surface adsorption sites in addition to interlayer exchange. Free chloride ions are efficiently captured through electrostatic attraction and complexation. The two curing pathways work together to form a dual-channel chloride ion capture mechanism of "interlayer embedding + surface complexation", which significantly improves the curing capacity and capture rate of the coating for chloride ions. The chloride ion curing amount reaches more than 60.8 mg / g and the chloride ion curing rate is more than 64.5%.
[0027] 3. The amidation reaction mediated by EDC and NHS coupling reagents anchors CDs to the surface of LDHs through stable covalent bonds (-CO-NH-), resulting in high bond strength. This prevents desorption and detachment under harsh service conditions such as long-term hydration, high alkalinity, and ion penetration, ensuring the long-lasting performance of the dual-channel curing function. This coating can extend the theoretically predicted service life of concrete structures by nearly double, with an improvement rate of 72-90%.
[0028] 4. Silica fume not only acts as a dispersion carrier for LDHs, but also reacts with cement hydration product Ca(OH)2 during the hydration process to generate CSH gel, which fills the internal pores and interfacial microcracks of the coating, significantly densifying the microstructure of the coating, and at the same time enhancing the interfacial bonding strength between the coating and the concrete substrate. The resulting dual protection mechanism of chemical curing and physical barrier comprehensively enhances the coating's resistance to chloride ion erosion.
[0029] 5. The reaction conditions in each step are mild and do not require complex and expensive equipment. The resulting CDs@LDHs composite material can be directly mixed with ordinary silicate cement in proportion and applied to the surface of steel bars or concrete using conventional construction methods such as spraying, brushing or scraping. The curing conditions are consistent with the existing concrete curing system. No additional special equipment or special processes are required, which makes it easy to promote and apply in engineering practice. The preparation process is simple and controllable. Attached Figure Description
[0030] Figure 1 This is a schematic diagram of the preparation process of grafting CDs onto LDHs according to the present invention;
[0031] Figure 2 These are physical images of the present invention, wherein a is a physical image of LDHs, b is a physical image of aminated LDHs, c is a physical image of CDs@LDHs composite material, d is a physical image of LDHs dispersion, e is a physical image of aminated LDHs dispersion, and f is a physical image of CDs@LDHs composite material dispersion.
[0032] Figure 3 This is a schematic diagram of CDs grafted onto LDHs according to the present invention;
[0033] Figure 4 These are SEM images of the present invention, wherein (a) is a SEM image of the reference concrete, (b) is a SEM image of LDHs modified concrete, (c) is a SEM image of CDs@LDHs composite modified concrete at a magnification of 1500, and (d) is a SEM image of CDs@LDHs composite modified concrete at a magnification of 3000. Detailed Implementation
[0034] Unless otherwise specified, all materials and reagents used in the following examples are commercially available. Experimental methods not specifically described in the examples are generally performed under standard conditions or as recommended by the manufacturer. Specifically, the LDHs were CaAl-LDH (catalog number 108309, size 0.5-2.5 μm), purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.; the silica fume was ultrafine silica fume with a particle size less than 1 μm, purchased from Xuzhou Mingrui Materials Co., Ltd.; the carbon dots had a particle size of 2-5 nm, purchased from Jiangsu Xianfeng Nanomaterials Technology Co., Ltd.; the silane coupling agent was KH-550 (CAS number: 919-30-2), purchased from Shanghai Maclean Biochemical Technology Co., Ltd.; the EDC coupling reagent was E106172, purchased from Aladdin; and the NHS coupling reagent was bis(NHS) activated ester of succinic acid, purchased from Aladdin.
[0035] Example 1
[0036] like Figure 1 A method for preparing a chloride ion resistant coating for concrete includes the following steps:
[0037] S1. Preparation of amino-functionalized LDHs:
[0038] Will Figure 2 LDHs powder of type a was dispersed in deionized water, and the concentration of the LDHs dispersion was controlled at 10 mg / mL. The dispersion was then ultrasonically dispersed at a frequency of 50 kHz for 40 min to obtain the LDHs dispersion. Figure 2 As shown in d. Silane coupling agent KH-550 was added to the above dispersion at a mass ratio of KH-550 to LDHs of 2:10. The mixture was stirred at 75 °C and 450 rpm for 8 h. After the reaction, the mixture was centrifuged, washed four times alternately with anhydrous ethanol and deionized water, and vacuum dried at 50 °C for 24 h to constant weight to obtain aminated LDHs (…). Figure 2 b).
[0039] S2. Preparation of silica fume pre-dispersed aminated LDHs:
[0040] Silica fume was added to deionized water at a mass ratio of 1:10, and ultrasonically dispersed at a frequency of 50 kHz for 40 min to obtain a silica fume dispersion. The amination-modified LDHs obtained in step S1 were added to the silica fume dispersion at a mass ratio of 1:2 (silica fume to LDHs), and stirred at 550 rpm for 60 min to ensure uniform loading of silica fume particles onto the LDHs surface, thus obtaining pre-dispersed silica fume LDHs.
[0041] Preparation and activation of S3 and CDs:
[0042] Carbon dots (CDs) with carboxyl-rich surfaces were prepared using a hydrothermal method. The CDs had a particle size of 2–5 nm, and a CDs solution with a concentration of 5 mg / mL was prepared. EDC / NHS was used as the coupling agent, with the molar ratio of EDC to carboxyl groups on the CDs surface controlled at 2:1 and the molar ratio of NHS to EDC at 1.5:1. The activation reaction was carried out at room temperature for 75 min, with the pH controlled at 5.5, forming an active ester intermediate, i.e., the activated CDs solution.
[0043] S4 and CDs grafted onto LDHs:
[0044] Under stirring conditions, the activated CDs solution was slowly added dropwise to the silica fume pre-dispersed aminated LDHs prepared in S2. The mass ratio of activated CDs to aminated LDHs was 1:12. The reaction was carried out at 42℃ and 450 rpm for 14 h with stirring. After the reaction, the mixture was centrifuged at 10000 rpm for 15 min, washed repeatedly with deionized water four times, and then freeze-dried at -45℃ and 30 Pa for 36 h to obtain the CDs@LDHs composite material. Figure 2 c.
[0045] S5. Preparation of concrete composite coating slurry:
[0046] The CDs@LDHs composite material prepared by S4 was mixed with ordinary silicate cement (P·O 42.5, Conch Cement) at a mass ratio of 1:4 and a water-cement ratio of 0.4. The mixture was stirred evenly to obtain a concrete composite coating slurry.
[0047] S6. Coating Application and Curing:
[0048] The composite coating slurry obtained from S5 was applied to the surface of the concrete structure by brushing, with a coating thickness of 2 mm. It was cured for 14 days at 25 ℃ and relative humidity ≥95% to obtain a concrete coating resistant to chloride ion erosion.
[0049] like Figure 31-Surface-aminated LDHs; 2-Silica fume particles; 3-Carbon dots (CDs). LDHs have a typical two-dimensional layered stacked structure. After surface amination modification, a large number of amino active sites are introduced into the layers, which not only retains the inherent interlayer ion exchange capacity of LDHs, but also provides reaction sites for covalent grafting of CDs. This is the structural basis for realizing the dual-channel chloride ion capture of "interlayer embedding and surface complexation". Silica fume particles are interspersed and dispersed between the amination LDH layers, playing a physical supporting role, opening up the interlayer spacing of LDHs, avoiding layer stacking and agglomeration, and ensuring that the interlayer ion exchange channels of LDHs are fully open, realizing the silica fume pre-dispersion strategy. In the later cement hydration, silica fume can also react with Ca(OH)2 to generate CSH, which densifies the material pores, builds a physical barrier, and strengthens the interface bonding between the coating and the concrete matrix; carbon dots are loaded and distributed on the surface of LDH layers. By relying on the active sites provided by the amino groups on the surface of LDHs, CDs can be grafted and fixed, avoiding carbon dot aggregation and loss. The carboxyl and hydroxyl groups carried by CDs provide a large number of surface adsorption sites, which work together with the interlayer ion exchange of LDHs to complete the chloride ion capture and curing.
[0050] like Figure 4 (a) The matrix of the reference sample exhibits significant macroscopic cracks, with prominent pores and microcracks. After the introduction of LDHs, the matrix cracks decreased compared to the reference group, and lamellar LDHs were distributed in the hydration products. However, LDHs still showed localized aggregation and stacking, failing to disperse sufficiently and uniformly. The matrix still contained many micropores, resulting in limited improvement in density. (See figure) Figure 4 (b). For example Figure 4 (c) After adding the CDs@LDHs composite material, large-sized cracks in the matrix basically disappeared, LDHs sheets were more uniformly dispersed in the matrix, hydration products intertwined, the overall density of the matrix was significantly improved, and silica fume participated in hydration to generate CSH gel, filling some pore defects and effectively repairing micro-defects; in addition, as Figure 4 (d) The CDs@LDHs sheets are tightly bonded to the cement hydration products, with good interfacial compatibility. The pores and microcracks are fully filled by the hydration gel, forming a dense and continuous microstructure.
[0051] Example 2
[0052] The remaining steps in this embodiment are the same as in Embodiment 1, except that: in step S1, the concentration of LDHs dispersion is 20 mg / mL, and in step S2, the mass ratio of silica fume to LDHs is 1:1.
[0053] Example 3
[0054] The remaining steps in this embodiment are the same as in Embodiment 1, except that: in step S1, the concentration of LDHs dispersion is 5 mg / mL, and in step S2, the mass ratio of silica fume to LDHs is 1:1.
[0055] Example 4
[0056] The remaining steps in this embodiment are the same as in Embodiment 1, except that: in step S3, the concentration of CDs solution is 1 mg / mL, and in step S4, the mass ratio of activated CDs to aminated LDHs is 1:5.
[0057] Example 5
[0058] The remaining steps in this embodiment are the same as in Embodiment 1, except that: in step S3, the concentration of CDs solution is 8 mg / mL, and in step S4, the mass ratio of activated CDs to aminated LDHs is 1:15.
[0059] Example 6
[0060] The remaining steps in this embodiment are the same as in Embodiment 1, except that: in step S3, the concentration of CDs solution is 10 mg / mL, and in step S4, the mass ratio of activated CDs to aminated LDHs is 1:20.
[0061] Example 7
[0062] A method for preparing a chloride ion resistant coating for concrete includes the following steps:
[0063] S1. Preparation of amino-functionalized LDHs:
[0064] LDHs powder was dispersed in deionized water to a concentration of 8 mg / mL. The dispersion was ultrasonically dispersed at 50 kHz for 40 min to obtain an LDHs dispersion. Silane coupling agent KH-550 was added to the dispersion at a mass ratio of 1:10 to KH-550 and the mixture was stirred at 300 rpm for 12 h at 60 °C. After the reaction, the mixture was centrifuged, washed four times alternately with anhydrous ethanol and deionized water, and then vacuum-dried at 40 °C for 12 h to constant weight to obtain amination-modified LDHs.
[0065] S2. Preparation of silica fume pre-dispersed aminated LDHs:
[0066] Silica fume was added to deionized water at a mass ratio of 1:5, and ultrasonically dispersed at 50 kHz for 40 min to obtain a silica fume dispersion. The amination-modified LDHs obtained in step S1 were added to the silica fume dispersion at a mass ratio of 1:3 (silica fume to LDHs), and stirred at 550 rpm for 60 min to ensure uniform loading of silica fume particles onto the LDHs surface, thus obtaining pre-dispersed silica fume LDHs.
[0067] Preparation and activation of S3 and CDs:
[0068] Carbon dots (CDs) with carboxyl-rich surfaces were prepared using a hydrothermal method. The CDs had a particle size of 2–5 nm, and a CDs solution with a concentration of 7 mg / mL was prepared. EDC / NHS was used as the coupling agent, with the molar ratio of EDC to carboxyl groups on the CD surface controlled at 2:1 and the molar ratio of NHS to EDC at 1:1. The activation reaction was carried out at room temperature for 75 min, with the pH controlled at 5.0, forming an active ester intermediate, i.e., the activated CDs solution.
[0069] S4 and CDs grafted onto LDHs:
[0070] Under stirring conditions, the activated CDs solution was slowly added dropwise to the silica fume pre-dispersed aminated LDHs prepared in S2. The mass ratio of activated CDs to aminated LDHs was 1:10. The reaction was carried out at 25°C and 450 rpm for 24 h with stirring. After the reaction was completed, the mixture was centrifuged at 10,000 rpm for 15 min, washed repeatedly with deionized water 4 times, and then freeze-dried at -50°C and 10 Pa for 48 h to obtain the CDs@LDHs composite material.
[0071] S5. Preparation of concrete composite coating slurry:
[0072] The CDs@LDHs composite material prepared by S4 was mixed with ordinary silicate cement at a mass ratio of 1:1 and a water-cement ratio of 0.3. The mixture was stirred evenly to obtain a concrete composite coating slurry.
[0073] S6. Coating Application and Curing:
[0074] The composite coating slurry obtained from S5 was applied to the surface of the concrete structure by brushing, with a coating thickness of 0.5 mm. It was cured for 7 days at 30℃ and relative humidity ≥95% to obtain a concrete coating resistant to chloride ion erosion.
[0075] Example 8
[0076] A method for preparing a chloride ion resistant coating for concrete includes the following steps:
[0077] S1. Preparation of amino-functionalized LDHs:
[0078] LDHs powder was dispersed in deionized water to a concentration of 15 mg / mL. The dispersion was ultrasonically dispersed at 50 kHz for 40 min to obtain an LDHs dispersion. Silane coupling agent KH-550 was added to the dispersion at a mass ratio of 3:10 to KH-550 and the mixture was stirred at 600 rpm for 4 h at 90 °C. After the reaction, the mixture was centrifuged, washed four times alternately with anhydrous ethanol and deionized water, and then vacuum-dried at 60 °C for 48 h to constant weight to obtain amination-modified LDHs.
[0079] S2. Preparation of silica fume pre-dispersed aminated LDHs:
[0080] Silica fume was added to deionized water at a mass ratio of 1:15, and ultrasonically dispersed at 50 kHz for 40 min to obtain a silica fume dispersion. The amination-modified LDHs obtained in step S1 were added to the silica fume dispersion at a mass ratio of 1:3 (silica fume to LDHs), and stirred at 550 rpm for 60 min to ensure uniform loading of silica fume particles onto the LDHs surface, thus obtaining pre-dispersed silica fume LDHs.
[0081] Preparation and activation of S3 and CDs:
[0082] Carbon dots (CDs) with carboxyl-rich surfaces were prepared using a hydrothermal method. The CDs had a particle size of 2–5 nm, and a CDs solution with a concentration of 3 mg / mL was prepared. EDC / NHS was used as the coupling agent, with the molar ratio of EDC to carboxyl groups on the CDs surface controlled at 2:1, and the molar ratio of NHS to EDC controlled at 2:1. The activation reaction was carried out at room temperature for 75 min, with the pH controlled at 6.5, forming an active ester intermediate, i.e., the activated CDs solution.
[0083] S4 and CDs grafted onto LDHs:
[0084] Under stirring conditions, the activated CDs solution was slowly added dropwise to the silica fume pre-dispersed aminated LDHs prepared in S2. The mass ratio of activated CDs to aminated LDHs was 1:18. The reaction was carried out at 60℃ and 450 rpm for 4 h with stirring. After the reaction was completed, the mixture was centrifuged at 10000 rpm for 15 min, washed repeatedly with deionized water 4 times, and then freeze-dried at -40℃ and 50 Pa for 24 h to obtain the CDs@LDHs composite material.
[0085] S5. Preparation of concrete composite coating slurry:
[0086] The CDs@LDHs composite material prepared by S4 was mixed with sulfoaluminate cement at a mass ratio of 1:8 and a water-cement ratio of 0.5. The mixture was stirred evenly to obtain a concrete composite coating slurry.
[0087] S6. Coating Application and Curing:
[0088] The composite coating slurry obtained from S5 was applied to the surface of the concrete structure by brushing, with a coating thickness of 3 mm. It was cured for 28 days at 20℃ and relative humidity ≥95% to obtain a concrete coating resistant to chloride ion erosion.
[0089] Comparative Example 1
[0090] Compared to Example 1, no CDs are added. Specifically:
[0091] S1: Preparation of pre-dispersed LDHs from silica fume
[0092] Predispersed silica ash LDHs were prepared using the same S1 step as in Example 1.
[0093] S2: Preparation of concrete composite coating slurry
[0094] The silica fume pre-dispersed LDHs obtained from S1 were mixed with ordinary silicate cement at a mass ratio of 1:4 and a water-cement ratio of 0.4. The mixture was stirred evenly to obtain a concrete composite coating slurry.
[0095] S3: Coating Application and Curing
[0096] A protective coating was obtained using the same coating and curing conditions as in Example 1.
[0097] Comparative Example 2
[0098] Compared to Example 1, no silica fume was added. Specifically:
[0099] S1: Preparation of CDs grafted with LDHs
[0100] (1) Preparation of amino-functionalized LDHs: The same method as in Example 1 was used to prepare amino-functionalized LDHs.
[0101] (2) Preparation and activation of CDs: The same CDs preparation and activation method as in Example 1 was used.
[0102] (3) CDs grafting: Under stirring conditions, the activated CDs solution was slowly added dropwise to aminated LDHs (without silica fume pre-dispersion). The mass ratio of activated CDs to aminated LDHs was 1:12. The reaction was carried out at 42℃ and stirred at 450 rpm for 14 h. After the reaction was completed, the mixture was centrifuged at 10000 rpm for 15 min, washed repeatedly with deionized water 4 times, and then freeze-dried at -45℃ and 30 Pa for 36 h to obtain the CDs@LDHs composite material.
[0103] S2: Preparation of concrete composite coating slurry
[0104] The CDs@LDHs composite material obtained from S1 was mixed with ordinary silicate cement at a mass ratio of 1:4 and a water-cement ratio of 0.4. The mixture was stirred evenly to obtain a concrete composite coating slurry.
[0105] S3: Coating Application and Curing
[0106] A protective coating was obtained using the same coating and curing conditions as in Example 1.
[0107] Comparative Example 3
[0108] Compared to Example 1, CDs are physically mixed and not grafted onto the surface of LDHs. Specifically:
[0109] S1: Preparation of pre-dispersed LDHs from silica fume
[0110] Predispersed silica ash LDHs were prepared using the same S1 step as in Example 1.
[0111] S2: Preparation of CDs@LDHs composite materials (physical mixing)
[0112] Carbon dots (CDs) with carboxyl groups rich in their surface were prepared using a hydrothermal method. The CDs had a particle size of 2–5 nm, and a CDs solution with a concentration of 5 mg / mL was prepared. Pre-dispersed LDHs from silica fume prepared in S1 were directly mixed with the CDs solution by physical stirring at a mass ratio of CDs to LDHs of 1:12. The mixture was stirred at 450 rpm for 14 h at 42 °C. After the reaction was complete, the mixture was centrifuged at 10,000 rpm for 15 min, washed four times with deionized water, and then freeze-dried at -45 °C and 30 Pa for 36 h to obtain the physically mixed CDs@LDHs composite material.
[0113] S3: Preparation of concrete composite coating slurry
[0114] The CDs@LDHs composite material obtained by S2 was mixed with ordinary silicate cement at a mass ratio of 1:4 and a water-cement ratio of 0.4. The mixture was stirred evenly to obtain a concrete composite coating slurry.
[0115] S4: Coating Application and Curing
[0116] A protective coating was obtained using the same coating and curing conditions as in Example 1.
[0117] The coatings and concrete properties obtained in Examples 1-6 and Comparative Examples 1-3 were tested, and the test results are shown in Table 1. Referring to the cement paste fluidity test method in GB / T 8077-2012 "Test Method for Homogeneity of Concrete Admixtures", the spread of the composite coating slurry obtained in each example and comparative example was determined to evaluate the workability and fluidity of the slurry. After the protective coatings obtained in each example and comparative example were cured to the specified age, samples were taken, ground, and passed through a 0.15 mm square-hole sieve. 5 g of the powder was placed in 100 mL of 3 mol / L NaCl solution and kept at a constant temperature and shaken for 24 h at 25℃. After filtration, the residual chloride ion concentration in the filtrate was determined by ion chromatography. The chloride ion curing amount (mg / g) per unit mass of coating material was calculated based on the difference between the initial concentration and the residual concentration. Chloride ion curing rate (%) = (initial chloride ion concentration - residual chloride ion concentration in filtrate) / initial concentration × 100%. The theoretical service life is predicted based on the time it takes for the steel reinforcement to rust, using Fick's second diffusion law. The effective diffusion coefficient of chloride ions in different samples is measured using the RCM test. Combined with the concrete cover thickness, the critical chloride ion concentration for steel reinforcement corrosion, and the chloride ion concentration on the environmental surface, the time it takes for the chloride ion concentration on the steel reinforcement surface to reach the critical concentration is calculated, which is the predicted service life. The theoretical predicted service life represents the improvement compared to the uncoated baseline.
[0118] Table 1 Properties of different coating slurries and concrete
[0119]
[0120] As shown in Table 1, the slurry spread of each embodiment is significantly better than that of the comparative example. Among them, the spread of Example 3 is the largest (240 mm), while the spread of Example 4 is relatively small (220 mm). This invention achieves uniform distribution of LDHs in the slurry through silica fume pre-dispersion, avoiding severe agglomeration of LDH nanosheets; simultaneously, CDs are covalently grafted onto the LDHs surface, acting as "nanospacers" to further prevent direct contact between particles, reducing internal friction and flocculation structure in the slurry, thereby significantly improving the slurry's fluidity and workability.
[0121] Although Comparative Example 1 contained silica fume pre-dispersed LDHs, it lacked the nano-spacer effect of CDs, resulting in limited LDH dispersion and low spread. Comparative Example 2, lacking silica fume pre-dispersion, experienced severe agglomeration of LDHs and CDs, increasing inter-particle friction within the slurry and achieving the lowest spread. In Comparative Example 3, CDs were introduced solely through physical mixing, lacking covalent bond anchoring. CDs easily migrated and re-agglomerated within the slurry, weakening the nano-spacer effect and resulting in lower spread than in the other examples.
[0122] The chloride ion curing amounts in Examples 1-6 were significantly higher than those in the three comparative examples. Specifically, Example 5 showed the highest chloride ion curing amount (71.6 mg / g), while Example 4 showed a relatively lower amount (60.8 mg / g). Examples 7 and 8 demonstrate that the temperature and time of vacuum drying had little effect on the chloride ion corrosion resistance of the final coating. The chloride ion curing rates in all examples were significantly higher than those in the three comparative examples.
[0123] When the concentration of the LDH dispersion was increased from 10 mg / mL (Example 1) to 20 mg / mL (Example 2), the slurry spread and chloride ion solidification amount decreased slightly, indicating that excessively high concentrations are not conducive to the full dispersion of LDHs, and partial agglomeration leads to a decrease in performance. When the concentration of the LDH dispersion was reduced to 5 mg / mL (Example 3), the spread increased to 240 mm, and the chloride ion solidification amount increased to 70.5 mg / g, indicating that lower dispersion concentrations are beneficial to the uniform dispersion of LDHs and the full opening of interlayer channels, thereby obtaining better chloride ion solidification performance.
[0124] As the concentration of CDs solution increased from 1 mg / mL (Example 4) to 5 mg / mL (Example 1) and 8 mg / mL (Example 5), the amount of chloride ion solidification increased slightly, indicating that appropriately increasing the amount of CDs can provide more surface adsorption sites and enhance the dual-channel solidification effect of "interlayer exchange + surface adsorption". However, when the concentration of CDs solution was further increased to 10 mg / mL (Example 6), the amount of chloride ion solidification decreased, and the spread also decreased slightly, indicating that excessive CDs may locally accumulate on the surface of LDHs, partially blocking the interlayer exchange channels, which has an adverse effect on chloride ion diffusion and adsorption. Therefore, the appropriate CDs solution concentration and CDs / LDHs ratio are the key to achieving the optimal dual-channel synergistic effect.
[0125] Compared to Comparative Example 1 (containing only silica fume pre-dispersed LDHs, without CDs), the chloride ion curing amount in Example 1 increased by approximately 110%. This is attributed to the introduction of CDs, which provides a large number of surface carboxyl and hydroxyl active functional groups. Through electrostatic attraction and complexation, additional surface adsorption channels are added beyond the interlayer exchange of LDHs, forming a dual-mode curing mechanism of "interlayer exchange + surface adsorption," which greatly improves the chloride ion capture capacity. Simultaneously, the nano-spacer effect of CDs fully opens the interlayer channels of LDHs, further enhancing the interlayer exchange efficiency. Compared to Comparative Example 2 (without silica fume pre-dispersion), the chloride ion curing amount in Example 1 increased by approximately 65%. In Comparative Example 2, LDHs and CDs agglomerated severely without silica fume pre-dispersion, obstructing the interlayer channels and preventing effective dispersion of CDs, hindering the dual-channel mechanism. In contrast, the silica fume pre-dispersion in each example fully opened the interlayer channels of LDHs, while CDs were uniformly dispersed and firmly anchored, ensuring the maximum utilization of the dual-channel curing function. Compared to Comparative Example 3 (where CDs were physically mixed rather than covalently grafted), the chloride ion curing amount in Example 1 was increased by approximately 53%. In Comparative Example 3, CDs were introduced only through physical mixing, lacking covalent anchoring. In the highly alkaline environment of hydration, they were prone to desorption, migration, and re-aggregation, resulting in a significant loss of surface adsorption sites. Furthermore, the aggregated CDs could not effectively function as nano-spacers, and the interlayer channels of LDHs were also somewhat blocked. In contrast, the CDs in each example were firmly anchored to the surface of the LDHs layer via amide covalent bonds, exhibiting high bonding strength. They were not easily detached under alkaline conditions during cement hydration, ensuring the long-term stability of surface adsorption sites and the persistent openness of interlayer channels. Therefore, the chloride ion curing performance was significantly superior to that of the physical mixing method.
[0126] In summary, this invention, through a synergistic strategy of "silica fume pre-dispersion + covalent grafting," successfully achieves uniform and stable dispersion of LDHs and CDs in cement-based coating systems. It fully leverages the dual-channel chloride ion curing mechanism of interlayer exchange and surface adsorption, while significantly improving the workability of the coating slurry. This technical solution provides an efficient and feasible approach for chloride erosion protection of marine concrete, cross-sea bridges, port terminals, and concrete structures in saline-alkali areas.
Claims
1. A method for preparing a chloride ion resistant coating for concrete, characterized in that, Includes the following steps: Step 1: Disperse layered bimetallic hydroxide powder in deionized water to obtain LDHs dispersion. Add silane coupling agent to LDHs dispersion, stir and heat to react, centrifuge, wash, and vacuum dry to obtain aminated LDHs. Prepare carbon dots with carboxyl groups on the surface using hydrothermal or microwave methods, prepare CDs solution, and activate the carboxyl groups on the surface of the carbon dots using EDC and NHS coupling agents to obtain activated CDs solution. Step 2: Add the aminated LDHs obtained in Step 1 to the silica fume dispersion and continue stirring and mixing to ensure that the silica fume particles are uniformly loaded on the surface of the LDHs, thereby obtaining silica fume pre-dispersed aminated LDHs. Step 3: Under stirring conditions, the activated CDs solution is added dropwise to the silica fume pre-dispersed aminated LDHs, and the CDs are grafted onto the surface of the LDHs layer through an amidation reaction. After the reaction is completed, the mixture is centrifuged, washed repeatedly with deionized water, and then freeze-dried to obtain the CDs@LDHs composite material. Step 4: Mix the CDs@LDHs composite material obtained in Step 3 with cement and stir evenly to obtain a concrete composite coating slurry. Step 5: Apply the composite coating slurry obtained in Step 4 to the surface of the steel reinforcement or concrete structure, and after curing, obtain a concrete anti-chloride ion erosion coating.
2. The method for preparing a concrete chloride ion erosion resistant coating according to claim 1, characterized in that: In step one, the concentration of the LDHs dispersion is 5~20 mg / mL.
3. The method for preparing a concrete chloride ion erosion resistant coating according to claim 1, characterized in that: In step one, the mass ratio of the silane coupling agent to the layered bimetallic hydroxide in the LDHs dispersion is 1~3:
10.
4. The method for preparing a concrete chloride ion erosion resistant coating according to claim 1, characterized in that: In step one, the stirring and heating reaction temperature is 60~90℃, the time is 4~12 h, the stirring rate is 300~600 rpm, the vacuum drying temperature is 40~60℃, and the drying time is 12~48 h.
5. The method for preparing a concrete chloride ion erosion resistant coating according to claim 1, characterized in that: In step one, the concentration of the CDs solution is 1~10 mg / mL, the molar ratio of NHS to EDC in the EDC / NHS coupling reagent is 1~2:1, and the pH of the activation treatment is 5.0~6.
5.
6. The method for preparing a concrete chloride ion erosion resistant coating according to claim 1, characterized in that: In step two, the silica fume dispersion is prepared by ultrasonic dispersion of silica fume and deionized water at a mass ratio of 1:5~15.
7. The method for preparing a concrete chloride ion erosion resistant coating according to claim 1, characterized in that: In step two, the mass ratio of silica fume to aminated LDHs is 1:1~3.
8. The method for preparing a concrete chloride ion erosion resistant coating according to claim 1, characterized in that: In step three, the mass ratio of the activated CDs solution to the silica fume pre-dispersed aminated LDHs is 1:5~20, the amidation reaction temperature is 25~60℃, and the time is 4~24 h; the freeze-drying temperature is -50~-40℃, the vacuum degree is 10~50 Pa, and the time is 24~48 h.
9. The method for preparing a concrete chloride ion erosion resistant coating according to claim 1, characterized in that: In step four, the mass ratio of CDs@LDHs composite material to cement is 1:1 to 8, and the cement is ordinary Portland cement with a water-cement ratio of 0.3 to 0.
5.
10. A concrete chloride ion resistant coating obtained by the preparation method according to any one of claims 1 to 9, characterized in that: The chloride ion curing content of the concrete anti-chloride ion coating is above 60.8 mg / g, and the chloride ion curing rate is above 64.5%.